Religions, Religious Moderation and Community Development and the Role of Higher Education to Strengthen It - Marde Christian Stenly Mawikere; Maison Immanuel Daud; Sudiria Hura; Grace Natalia Birahim; Virginia Rebeca Tulung (Peneliti.net, 2023)
Religion has a significant contribution to social, economic and political development. By promoting moral and ethical values, religion is able to form a collective consciousness to promote harmony and harmony in society. In addition, religion is also a driving force in poverty alleviation, education, health, and environmental protection. However, it should be remembered that excessive religious influence can lead to extremism and disrupt social stability. Therefore, the development of religious moderation is important to maintain a balance between spiritual beliefs and the demands of modern progress, while fostering interreligious dialogue and intercultural interaction to encourage mutual respect and sustainable development. This article analyzes the role of religion in development as the development of religious moderation. In a complex and multicultural global context, the role of religion in providing moral and ethical guidance is crucial for achieving sustainable social progress. However, it is necessary to be aware of the risk of extremism and intolerance which could hinder development. Therefore, this article highlights the importance of interfaith dialogue and inclusivity in ensuring the positive contribution of religion and creating a peaceful and stable society. The results of the analysis in this article are expected to provide guidance for society and especially the world of higher education to optimize the role of religion in achieving inclusive and sustainable development goals